Assessment of heavy metal pollution in the Straits of Johore by using transplanted caged mussel, Perna viridis - Ng, Eugene Yew Jing; Yap, Chee Kong; Zakaria, Mohamad Pauzi; Tan, Soon Guan (Universiti Putra Malaysia Press, 2013)
In this study, a polluted site at Kg. Pasir Puteh was assessed for heavy metal pollution by using transplanted caged mussel (Perna viridis) from a relatively clean population, Sg. Melayu; both are located in the Strait of Johore. For control purposes, the P. viridis from Kg. Pasir Puteh were also simultaneously transplanted in Sg. Melayu at the same time. It was found that Zn was the metal which got accumulated fastest in the transplanted mussel while Cd was the slowest. This study indicated that the byssus of Perna viridis was most effective for biomonitoring of Cd, Ni, Pb and Zn, while the shell could be used for the biomonitoring of Cu, Ni and Pb and the total soft tissue for the biomonitoring of Ni since they were able to accumulate and eliminate the respective metals well. By using mussel as a biomonitor, the present study found that Kg. Pasir Puteh, which is located in the eastern part of the Strait of Johore, had significantly higher contamination and bioavailabilities of Cd, Cu, Fe, Ni, Pb and Zn. Therefore, the use of the transplanted caged mussels is very useful for heavy metal assessment purposes since it can increase the validity of data interpretation by minimizing ecological factors.